Eco-innovation drivers and their impact on tourism and the hospitality business in Egypt - Mohamed Ahmed; Nadir Aliane; Nourredine Khababa; Maha Y. K. Abdou; Mohamed Fathy Agina (Administrative Sciences, 2023)
This research aims to examine the mediating effects of eco-innovation practices in the relationship between the drivers of eco-innovation and the performance of tourism and hospitality enterprises. A quantitative approach was adopted in this research using questionnaire surveys as an instrument for collecting primary data. Based on the convenience sampling technique, a total of 550 questionnaire forms were distributed to five-star hotels and travel agencies in Cairo. Out of the distributed forms, only 400 forms were filled out and returned to the researchers and thus valid for analysis, representing a response rate of 72.7%. Structural Equation Modeling (SEM) using partial least squares (PLS-SEM) was employed to test the research model. The results showed the significant effect of independent variables on dependent variables through mediating variables. Multiplied path coefficients were used to measure the confidence interval (CI) for measuring the mediating relationship. The results supported the effect of eco-innovation practices as a mediating factor in the relationship between the drivers of eco-innovation and the performance of tourism and hospitality enterprises. The findings also showed that the eco-innovation drivers, which include management awareness, organizational capabilities, and environmental strategy, have a significant effect on eco-innovation practices and tourism/hospitality enterprise performance when integrating the mediating variables of eco-innovation practices. There are a few studies that have also examined a conceptual framework to examine eco-innovation practices as mediating factors in the relationship between the drivers of eco-innovation and the performance of tourism and hospitality enterprises in terms of five-star hotels and travel agencies in Egypt. Consequently, this research contributes to the literature related to tourism and hospitality management through highlighting the mediating effect of eco-innovation practices on the relationship between the drivers of eco-innovation and the performance of tourism and hospitality enterprises.
Keywords: 350; eco-innovation; eco-innovation drivers; Egypt; hotels; performance; practices; travel agent